Emotional Distraction and Bodily Reaction: Modulation of Autonomous Responses by Anodal tDCS to the Prefrontal Cortex - Schroeder, Philipp A.; Ehlis, Ann-Christine; Wolkenstein, Larissa; Fallgatter, Andreas J.; Plewnia, Christian (Frontiers in Cellular Neuroscience, 2015)
Prefrontal electric stimulation has been demonstrated to effectively modulate cognitive processing. Specifically, the amelioration of cognitive control over emotional distraction by transcranial direct current stimulation (tDCS) points towards targeted therapeutic applications in various psychiatric disorders. In addition to behavioral measures, autonomous nervous system (ANS) responses are fundamental bodily signatures of emotional information processing. However, interactions between the modulation of cognitive control by tDCS and ANS responses have received limited attention. We here report on ANS data gathered in healthy subjects that performed an emotional cognitive control task parallel to the modulation of left prefrontal cortical activity by 1mA anodal or sham tDCS. Skin conductance responses (SCRs) to negative and neutral pictures of human scenes were reduced by anodal as compared to sham tDCS. Individual SCR amplitude variations were associated with the amount of distraction. Moreover, the stimulation-driven performance- and SCR-modulations were related in form of a quadratic, inverse-U function. Thus, our results indicate that non-invasive brain stimulation (i.e., anodal tDCS) can modulate autonomous responses synchronous to behavioral improvements, but the range of possible concurrent improvements from prefrontal stimulation is limited. Interactions between cognitive, affective, neurophysiological, and vegetative responses to emotional content can shape brain stimulation effectiveness and require theory-driven integration in potential treatment protocols.